Exploring Higher Capital Requirements in Nepal Under Basel III: A Qualitative Approach - Anuj Acharya; Bidush Nepal; Ananta Raj Kafle (CV. Literasi Indonesia, 2023)
This paper explored the impact of capital regulation on the banking industry in Nepal and sought to understand the reasons behind the requirements for higher capital in the country compared to global standards set by the Basel Committee on Banking Supervision (BCBS). The paper incorporated semi-structured interviews with experts from banks and the Nepal Rastra Bank (NRB) and employed thematic analysis to analyze the responses. The main factors driving higher capital requirements in Nepal were identified as risk management practices, financial stability, and the cost of financing, including the supervisory review process and the internal control systems of banks. The study found that the banking industry in Nepal lacks strong risk management policies and practices and that the regulator places a greater emphasis on ensuring the stability and resilience of banks rather than minimizing the economic cost of financing. Additionally, the corporate governance and internal control systems of banks in Nepal were found to be suboptimal.